2014
DOI: 10.1118/1.4881319
|View full text |Cite
|
Sign up to set email alerts
|

Automatic segmentation for detecting uterine fibroid regions treated with MR-guided high intensity focused ultrasound (MR-HIFU)

Abstract: The results suggest that the segmentation algorithm developed, requiring no user-input, provides a feasible and practical approach for the automatic evaluation of the boundary and volume of the HIFU-treated region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…28,29 Enhanced MRI was considered an important evaluation measure for the early therapeutic response of uterine fibroids to HIFU. 18,30,31 The extent of the nonperfused volume or nonperfused volume ratio obtained from posttreatment enhanced MRI was significantly correlated with the treatment outcome for uterine fibroids. 31 An increase in the nonperfused volume ratio was associated with an increase in the fibroid volume reduction ratio and symptomatic relief.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…28,29 Enhanced MRI was considered an important evaluation measure for the early therapeutic response of uterine fibroids to HIFU. 18,30,31 The extent of the nonperfused volume or nonperfused volume ratio obtained from posttreatment enhanced MRI was significantly correlated with the treatment outcome for uterine fibroids. 31 An increase in the nonperfused volume ratio was associated with an increase in the fibroid volume reduction ratio and symptomatic relief.…”
Section: Discussionmentioning
confidence: 97%
“…It has been revealed that HIFU has a therapeutic effect on uterine fibroids mainly by causing coagulation necrosis of targeted tissue, which was presented as a nonenhancement characteristic on enhanced MRI . Enhanced MRI was considered an important evaluation measure for the early therapeutic response of uterine fibroids to HIFU . The extent of the nonperfused volume or nonperfused volume ratio obtained from posttreatment enhanced MRI was significantly correlated with the treatment outcome for uterine fibroids .…”
Section: Discussionmentioning
confidence: 99%
“…Other mixed methods: Antila et al [38] designed an automatic segmentation pipeline without user input. They applied the active shape model (ASM) to get the deformed surface, and classified PV (perfused volume: the untreated tissue) and NPV (non-perfused volume: the treated tissue) by an expectation maximization (EM) algorithm.…”
Section: A Conventional Methods Of Uterus and Uterine Fibroid Segmenmentioning
confidence: 99%
“…Image registration steps are mandatory and are performed using the external software tool Medical Image Processing, Analysis, and Visualization (MIPAV) [397]. In [22], an automatic method for treated fibroid segmentation is proposed. Both the post-operative CE-MR image stack (interpolated to a 3D volume) and the treatment plan (i.e., file that stores the sonication cells used during the MRgFUS treatment) are required.…”
Section: Mrgfus Treatments For Uterine Fibroidsmentioning
confidence: 99%